Odnos "visokošolski knjižničar - študent" - Vidic, Mira (Knjižnica, 2010)
An academic library is supposed to provide quality services to the students, faculty employees and others. The students, who constitute the majority of the users, often seem to lack the skills and knowledge necessary to navigate and locate items within the library during this crucial period of life between education and employment. University librarians play a key role in explaining all the services of an academic library. A library is used by students mostly as a place to study, wait for their classes to start or search for the necessary literature. A question arose: how well do the students know the duties of academic librarians and how to encourage them to learn more about their work and find out what these information technology experts can offer? Students of the University of Ljubljana have been interviewed to determine that. 98 students of the average age of 23 years were interviewed in December 2008 and January 2009. The results showed their poor knowledge of academic libraries as most of the students do not know how many people are employed there and what their skills and everyday duties are. They do believe, however, that the professors encourage them to visit the library, but sadly do not perceive the librarians as qualified assistants of the faculty and only seldom credit them for their part in achieving their scholastic performance. We can therefore conclude that academic librarians are not key persons to the students during the time of attending the university. The academic library should try harder to emphasize its prominence and role in tertiary education as a key factor in information literacy - an important part of lifelong learning.
Keywords: visokošolske knjižnice; knjižničarji; student; študenti; medosebni odnosi